Equity in the age of statutes - TANG, Hang Wu (Institutional Knowledge at Singapore Management University, 2015)
It has been said that we have moved from a legal system dominated by the common law to one where statutes represent the primary source of the law. Where does that leave equitable jurisprudence in the age of statutes? This article examines the tricky interplay between statute law and equity. It is suggested that there are broadly three categories of cases when the court is considering the application of equitable doctrines in the context of a statute. First, the statute may explicitly or implicitly abolish the application of a relevant equitable doctrine. In this case, the relevant equitable doctrine should not be used because this would undermine the legislative intent of the statute. Second, the statute may expressly incorporate equitable concepts. Examples of these are statutes which expressly incorporate the concept of unconscionability or are premised on relief being granted on “just and equitable” grounds. Here, there are no objections to the courts using equitable concepts. Finally, the statute is equivocal about the application of equitable doctrines. In these cases, the courts should first determine the purpose of the statute and assess whether the application of the relevant equitable doctrine would undermine the purpose of the statute. If the purpose of the statute is not undermined, the courts should be free to resort to equitable doctrines in order to resolve the dispute. In some cases, the extent in which the equitable doctrine is applicable may be limited by the statute.